What role does personality play? : First results on occupational differences and wages from a recent BIBB survey - Rohrbach-Schmidt, Daniela [Verfasser]; Ebner, Christian [Verfasser] (My University, 2019)
"The study of personality traits has received increasing attention in education and labour market research in recent years. Numerous studies show that personality exerts an independent influence on educational and labour market success. Against this background, a BIBB research project surveyed around 8,000 core employees from the BIBB/BAuA Employment Survey 2018 on their personality traits. Which personality structures and preferences exist in the current working population in Germany? Are there any differences in these structures between occupational groups? What significance do these characteristics have for labour market success? These are the issues addressed in this article." (authors' abstract; BIBB-Doku)
Keywords: G 1.3.3 Bildungs- & Erwerbsbiografien; G 2.4.1 Bildungs- und Berufswege; Berufsverlauf; Beruflicher Aufstieg; Berufserfolg; BIBB-/BAuA-Erhebung; Erwerbstätiger; Persönlichkeitsstruktur; Persönlichkeitsmerkmal; Persönlichkeitsentwicklung; Lohnstruktur